Mass Production of Highly Active NK Cells for Cancer Immunotherapy in a GMP Conform Perfusion Bioreactor - Bröker, Katharina; Sinelnikov, Evgeny; Gustavus, Dirk; Schumacher, Udo; Pörtner, Ralf; Hoffmeister, Hans; Lüth, Stefan; Dammermann, Werner (Frontiers in Bioengineering and Biotechnology, 2019)
NK cells have emerged as promising candidates for cancer immunotherapy, especially due to their ability to fight circulating tumor cells thereby preventing metastases formation. Hence several studies have been performed to generate and expand highly cytotoxic NK cells ex vivo, e. g. by using specific cytokines to upregulate both their proliferation and surface expression of distinct activating receptors. Apart from an enhanced activity, application of NK cells as immunotherapeutic agent further requires sufficient cell numbers and a high purity. All these parameters depend on a variety of different factors including the starting material, additives like cytokines as well as the culture system. Here we analyzed PBMC-derived NK cells of five anonymized healthy donors expanded under specific conditions in an innovative perfusion bioreactor system with respect to their phenotype, IFNγ production and cytotoxicity in vitro. Important features of the meander type bioreactors used here are a directed laminar flow of medium and control of relevant process parameters. Cells are cultivated under “steady state” conditions in perfusion mode. Our data demonstrate that expansion of CD3+ T cell depleted PBMCs in our standardized system generates massive amounts of highly pure (>85%) and potent anti-cancer active NK cells. These cells express a variety of important receptors driving NK cell recruitment, adhesion as well as activation. More specifically, they express the chemokine receptors CXCR3, CXCR4 and CCR7, the adhesion molecules L-selectin, LFA-1 and VLA-4, the activating receptors NKp30, NKp44, NKp46, NKG2D, DNAM1 and CD16 as well as the death ligands TRAIL and Fas-L. Moreover, the generated NK cells show a strong IFNγ expression upon cultivation with K562 tumor cells and demonstrate a high cytotoxicity towards leukemic as well as solid tumor cell lines in vitro. Altogether, these characteristics promise a high clinical potency of thus produced NK cells awaiting further evaluation.